2014
DOI: 10.22495/cocv12i1p4
|View full text |Cite
|
Sign up to set email alerts
|

Developing a model to evaluate the information technology competence of boards of directors

Abstract: IT governance is critical in the current business environment. Boards of directors are ultimately responsible for ensuring the entities they control have appropriate IT facilities. This study develops a model of IT competences boards should have, to achieve appropriate IT governance. The model is then pilot tested, using Ireland as a case study, to evaluate two issues. Firstly, whether these are the appropriate competences current boards need and second, whether boards appear to have those competences. A surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This can results competence breaches which helps the boards to have well understanding on the governance of IT. Nonetheless allow the boards to http: //dx.doi.org/10.15405/epsbs.2018.05.23 Corresponding Author: Amalia Mukhlas Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 285 deliberate the influence of IT structure on board IT governance processes (Mohamad et al, 2014). A study performed by #1 suggested a new structure to be proposed to replace the current one.…”
Section: Proper Structure For It To Achieve Itg Level and Decision Mamentioning
confidence: 99%
See 1 more Smart Citation
“…This can results competence breaches which helps the boards to have well understanding on the governance of IT. Nonetheless allow the boards to http: //dx.doi.org/10.15405/epsbs.2018.05.23 Corresponding Author: Amalia Mukhlas Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 285 deliberate the influence of IT structure on board IT governance processes (Mohamad et al, 2014). A study performed by #1 suggested a new structure to be proposed to replace the current one.…”
Section: Proper Structure For It To Achieve Itg Level and Decision Mamentioning
confidence: 99%
“…Therefore, clear guidelines and structure to manage and govern the IT infrastructure is important. The IT governance (ITG) is paving the way to ensure all stakeholders understand their roles and responsibilities (Mohamad, Hendrick, O'Leary, & Best, 2014) in managing IT to achieve organisation's missions and goals. In addition, the adoption of IT governance can be a key factor to enable continuous organisational performance (Ajayi & Hussin, 2014).…”
Section: Introductionmentioning
confidence: 99%